Second hand spaces : über das Recycleln von Orten im städtischen Wandel = Second hand spaces - Ziehl, Michael; Osswald, sarah; Hasemann, Oliver; Schnier, Daniel (Berlin : Jovis Berlin, 2012)
In this volume, 27 urban planning experts highlight the backgrounds, users and effects of so-called "second hand spaces"--vacant sites which have been repurposed in areas undergoing urban change. The new functions of these spaces range from activities as simple as sunbathing in a defunct swimming pool to the installation of an open-air boxing ring
German, English
boek